Nas fronteiras do habitar horizontino: significados, sentidos e representações no modo de morar moderno - Daniela Batista Lima Barbosa (2020)
The question of this research deals with the effects of the modernization of the 19th century that can be verified in the materializations of the way of living and in the architecture of the house in Belo Horizonte. The research deals with modernization as a process and investigates the way of life of the village and the city from the analysis of the collections of architectural plans in the Public Archive of the City of Belo Horizonte (APCBH) and in the Public Archive of Minas Gerais (APM). The research adopts the investigation of the changes between the frontiers between the public and the private, one of the aspects of the 19th century modernization process, as a way of approaching the horizon dwelling in its transformations in daily life and in the way of living. The first approach relates the way of living and the legal and administrative modernizing measures of access to land in the village and in the capital. The second approach relates the links between sociability, work, home environments and the frontiers of public and private and the practices of civility and the materializations of modernity in the late 19th century and early 20th century. The third approach takes place through the verification of the constant ambiences in the horizontine houses of the village and the capital, in their annexes and in their immediate surroundings. From the documentary research in the collections of the Public Archive of the City of Belo Horizonte (APCBH) and the Public Archive of Minas Gerais (APM), a set of significant architectural plans of the way of inhabiting the village and the city of Belo Horizonte is selected. This set of plans comprises two collections: the plans of the properties in Arraial and surroundings prepared by the New Capital Construction Commission and the architectural plans approved in the new capital. The research points out, at the end of the 19th century and in the first two decades of the 20th century, the private and the public as domains that converge in a complex and codified horizonine dwelling translated into the limits and precise dimensions of the lots, in the implantation of the Arraialense house together the streets with extensive backyards, in the lateral and frontal setbacks of the implantation of the house of the capital, in the architectural program and in the elements of the architecture of the house. The social and cultural changes within the scope of modernization in the late 19th and early 20th centuries can be seen in the way of life that embraces the rules of civility and elegant living.